20-year-old injury: an unusual cause of stroke. (20th April 2013) - Lim, V W L; Flynn, C A; O'Connor, M; Lyons, D
Abstract : A 62-year-old man presented with a 2-day history of headache, nausea and dizziness on a background of recently diagnosed stage 2c prostate carcinoma and controlled hypertension. Imaging confirmed bilateral cerebellar strokes; on further investigations, he was found to have undiagnosed subclavian steal syndrome following severe injury to his left arm more than 20 years earlier.